Tejano legacy : rancheros and settlers in south Texas, 1734-1900 - Alonzo, Armando C. (University of New Mexico Press, 1998)
This is a study of Tejano ranchers and settlers in the Lower Rio Grande Valley from their colonial roots to 1900. The first book to delineate and assess the complexity of Mexican-Anglo interaction in South Texas, it also shows how Tejanos continued to play a leading role in the commercialization of ranching after 1848 and how they maintained a sense of community.
Keywords: Lower Rio Grande Valley (Tex.) -- History.; Frontier and pioneer life -- Texas -- Lower Rio Grande Valley.; Ranchers -- Texas -- Lower Rio Grande Valley -- History.; Mexicans -- Texas -- Lower Rio Grande Valley -- History.; Land tenure -- Texas -- Lower Rio Grande Valley -- History.; Lower Rio Grande Valley (Tex.) -- Ethnic relations.; Basse vallée du Rio Grande (Tex.) -- Histoire.; Ranchers -- Texas -- Basse vallée du Rio Grande -- Histoire.; Mexicains -- Texas -- Basse vallée du Rio Grande -- Histoire.; Basse vallée du Rio Grande (Tex.) -- Relations interethniques.; HISTORY -- State & Local -- General.; Ethnic relations; Frontier and pioneer life; Land tenure; Mexicans; Ranchers; Texas -- Lower Rio Grande Valley; Kolonisten.; Frontier.; Vie des pionniers -- Texas (États-Unis); Ranchers -- États-Unis -- Texas (États-Unis) -- Histoire.; Propriété foncière -- Texas (États-Unis) -- Histoire.; Mexicains -- États-Unis -- Texas (États-Unis) -- Histoire.; Rio Grande, Vallée du -- Histoire.; Texas (États-Unis) -- Relations interethniques.; History